1976
DOI: 10.1126/science.194.4268.949
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosic Microfibrils: Nascent Stages of Synthesis in a Higher Plant Cell

Abstract: Freeze-fracturing of untreated plasma membrane and inner wall surfaces of stelar tissue in corn roots demonstrated the association of globular complexes with the ends of nascent microfibrils. It is proposed that the granule complexes associated with the outer leaflet of the plasma membrane coordinate the assembly of the cellulosic microfibrils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…Cellulose microfibrils are synthesized by a large membrane-bound protein complex. In the land plants and charophycean algae, the cellulose synthesis complex (CSC) has a "rosette" shape (Mueller et al, 1976;Mueller and Brown, 1980b;Kimura et al, 1999), and the entire CSC has reported diameters between 24 to 30 nm (Lerouxel et al, 2006). This structural information was revealed by freeze-fracture transmission electron microscopy, showing six lobes in a hexagonal arrangement at the point where the transmembrane helices of multiple cellulose synthase proteins (CESAs) cross the plasma membrane.…”
mentioning
confidence: 99%
“…Cellulose microfibrils are synthesized by a large membrane-bound protein complex. In the land plants and charophycean algae, the cellulose synthesis complex (CSC) has a "rosette" shape (Mueller et al, 1976;Mueller and Brown, 1980b;Kimura et al, 1999), and the entire CSC has reported diameters between 24 to 30 nm (Lerouxel et al, 2006). This structural information was revealed by freeze-fracture transmission electron microscopy, showing six lobes in a hexagonal arrangement at the point where the transmembrane helices of multiple cellulose synthase proteins (CESAs) cross the plasma membrane.…”
mentioning
confidence: 99%
“…cell walls | CESA complexes | cell expansion | microtubules | polysaccharides C ellulose is synthesized at the plasma membrane by hexameric protein complexes with a diameter of 25-30 nm when observed by freeze-fracture electron microscopy in algae, moss, and vascular plants (1)(2)(3)(4). The only known component of the complexes is cellulose synthase (CESA), which is represented by 10 isoforms in Arabidopsis (5).…”
mentioning
confidence: 99%
“…This low density in vesiculated regions suggests that membrane surfaces had increased perhaps accompanied by lipid synthesis or the incorporation of lipid molecules which did not include the migration of intramembrane particles from the centre towards the vesiculated regions. Mueller et al (16). The following reasons strongly suggest that the hexagonal arrays of Micrasterias crux-melitensis are not artefacts but may be involved in the production of cell wall microfibrils.…”
Section: Discussionmentioning
confidence: 99%
“…However, these sections provide little information about the particles embedded in membranes. Recently, the structural relationship between cell wall microfibrils and plasma membrane particles has been pointed out using the freeze-fracture technique (10,14,16,18,19). In our study, intramembrane particles of dictyosomes, LVs and plasma membranes were examined by the freeze-fracture technique in order to gain further insight into cell wall synthesis and related questions.…”
Section: Micrasteriasmentioning
confidence: 99%